The Bioactivated Interfacial Behavior of the Fluoridated Hydroxyapatite-Coated Mg-Zn Alloy in Cell Culture Environments - Jianan Li; Lei Cao; Yang Song; Shaoxiang Zhang; Changli Zhao; Fan Zhang; Xiaonong Zhang (Bioinorganic Chemistry and Applications)
A partially fluorine substituted hydroxyapatite- (FHA-) coated Mg-Zn alloy was prepared to investigate the interfacial behavior of degradable Mg-based biomaterials with degradable bioactive coatings in a cell culture environment. Peaks from the results of X-ray diffraction (XRD) were characterized and compared before and after cell culture. It was found that Ca-P, including poorly crystalline ion-substituted Ca-deficient HA (CDHA), was formed in greater amounts on the interface of coated samples compared with the uncoated ones. A thermodynamic mechanism for Ca-P formation on biodegradable Mg alloys in a cell culture environment is proposed. Combined with improved cell calcification, the-FHA coated Mg alloys have the ability to promote CDHA formation, as expected thermodynamically. It is suggested that the specific cell culture environment and the bone-like FHA coatings together facilitate the observed behavior. Moreover, cell culture environment probably increased the biomineralization to a detectable level by affecting the kinetics of apatite formation.